Grammar exercises - Rein, David (Vermont Pro Lingua Associates, 1986)
Grammar Exercises I & II Varied, vocabulary-rich, with answers in the book by: Arthur A. Burrows Levels: Secondary, University, Adult Contextualized exercises, varied, vocabulary-rich, with the answers in the book Part One for elementary and intermediate students by Arthur A. Burrows Part Two for intermediate students by David P. Rein Each book covers the same grammar as the corresponding Grammar Handbook, point for point, so the exercises can be used as homework by students using the Handbook in class. These books can also be used independently by teachers who want to do grammar out of class, saving class time for more communicative work. Each lesson is rich in vocabulary and contextualized information that will interest students in high school, university, and adult programs. Answers are in the back, giving students immediate feedback.